PENGARUH OUTDOOR LEARNING TERHADAP KECERDASAN INTERPERSONAL PADA ANAK USIA 5-6 TAHUN DI TK ISLAM BAITURRAHMAN KECAMATAN RUMAI PESISIR KOTA PEKANBARU - Putri, Rossy Arnova; Chairilsyah, Daviq; Febrialismanto, Febrialismanto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This study aims to determine the effect of outdoor learning towards interpersonal intelligence of children aged 5-6 years in TK Islam Baiturrahman Rumbai Pesisir sub district Pekanbaru city. The method of this research used experimental method with using one group pre-test post-test design. The samples used in this study were 17 students. The data collection technique used is observation. Technique of data analysis used t-test by using program of SPSS 17. The research hypothesis was to find the influence of outdoor learning towards interpersonal intelligence of children aged 5-6 years in TK Islam Baiturrahman Rumbai Pesisir sub district Pekanbaru city. Based on data analysis was known that tcalculated = 32.250 > ttable = 2.120 with Sig. (2-tailed) = 0.000. Because Sig < 0.05 it can be concluded that there is difference of interpersonal intelligence that was be done before and after of outdoor learning. It can be interpreted that there is influence of outdoor learning activity towards interpersonal intelligence of children aged 5-6 years in TK Islam Baiturrahman Rumbai Pesisir sub district Pekanbaru city significant that is equal to 47.46%.Keyword : Interpersonal Intelligence, Outdoor Learning